Approach bias modification reduces automatic gaming tendencies and enhances brain synchronization in internet gaming disorder - Wei, Meiting; Luo, Xin; Fu, Jiejie; Dong, Yi-Sheng; Liu, Jiang; Li, Xuzhou; Dong, Guang-Heng (Journal of psychiatric research, 2025)
Automatic approaches to gaming-related cues are key factors in internet gaming disorder (IGD). Approach bias modification (ApBM) has been shown to reduce addictive behaviors, but its neurobiological effects remain poorly understood. This study examined changes in brain activities in the ‘natural’ state in IGD patients after ApBM. Fifty-five (of 61) IGD patients were randomly assigned to the approach–avoidance task (AAT, n = 30) and sham-AAT (n = 25) groups. Participants completed the pre-test, five real/sham ApBM sessions, and the post-test. In the pre-and post-tests, fMRI data were collected while viewing gaming and neutral videos. Inter-subject correlation (ISC) and functional connectivity (FC) analyses were conducted to explore the ApBM-related changes. ANOVA of behavioral data revealed that ApBM significantly decreased the approach bias and addiction scores. The ISC analyses revealed increased synchronization in the paracentral lobule, precuneus, and insula regions in the ATT group after ApBM. Additionally, decreased FC was observed between the insula and superior frontal gyrus, precuneus, and orbitofrontal cortex in the AAT group. Preliminary findings suggest that ApBM may be effective in reducing automatic approach tendencies toward gaming cues, highlighting its potential as an intervention strategy. However, it is important to note that the neurobiological evidence in this study only provides a possible association, and the results should be interpreted with caution. Future research is needed to further examine the clinical efficacy of ApBM in IGD, whether as a stand-alone treatment or as an adjunct to formal therapy. •IGD patients exhibit a bias tendency towards gaming cues, and ApBM appears to alleviate this bias.•ApBM enhanced brain synchronization in executive control regions and reduced reward-FC.•Findings suggest the potential of ApBM in IGD, but require further studies for clinical validation.